Frequency of Acute Kidney Injury in Patients Presenting with Acute Coronary Syndrome and its Relationship with in-Hospital Mortality - Ali, Shabahat; Umar, Rana Muhammad; Yaqub Pannu, Furqan; Ali, Faryad; Saboor, Qazi Abdul; Ahmed, Bilal (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Acute Kidney Injury (AKI) is a significant concern in patients with Acute Coronary Syndromes (ACS), including both ST Elevation Myocardial Infarction (STEMI) and Non-ST Elevation Myocardial Infarction (NSTEMI), due to its association with increased in-hospital mortality. Despite its critical impact, existing data on AKI in ACS patients is limited and often lacks local context. This study addresses this gap by investigating the frequency of AKI in myocardial infarction patients and its relationship with in-hospital mortality, providing valuable insights for local healthcare practices and patient management strategies. Objective: To determine frequency of AKI in patients with ACS and to compare in-hospital mortality in patients of ACS with versus without AKI. Settings: Cardiology Department, Shaikh Zayed Hospital Lahore Duration: Nine months w.e.f 01-Jan to 30-Sept, 2021 Methodology: The study encompassed one hundred seventy (170) patients with various forms of ACS, such as STEMI and non-NSTEMI. Demographic were noted after taking informed written consents. The patients underwent required lab tests and data was recorded. Two groups were assimilated as group A (non-AKI group) and group B (AKI group). In hospital mortality was noted and compared between the groups using SPSS version 21. Results: In this study, AKI was found in 24.7% of patients with myocardial infarction. Group A, comprising 128 patients without AKI, had a mean age of 61.62 ± 10.19 years, while Group B, with 42 AKI patients, had a mean age of 62.18±9.94 years, with no significant age difference (p=0.651). Gender distribution showed 70.3% of Group A patients were male, versus 80.9% in Group B, though this difference was insignificant (p=0.210). BMI distribution was also similar across groups, with no significant difference (p=0.321). Hemoglobin levels were significantly lower in Group B (131.6 ± 25.04 g/L) compared to Group A (141.9 ± 18.41 g/L, p=0.001). Serum creatinine was notably higher in Group B (188.07 ± 85.94 μmol/L) compared to Group A (101.91 ± 30.84 μmol/L, p=0.001). Group B also had lower ejection fraction and reduced glomerular filtration rate. The in-hospital mortality rate was significantly high in Group B (26.1%) compared to Group A (4.7%), p<0.05. Conclusion: In this study, patients with AKI had significantly higher in-hospital mortality compared to those without AKI. This disparity, coupled with lower hemoglobin levels, elevated serum creatinine, higher triglycerides, reduced ejection fraction, and diminished baseline glomerular filtration rate in Group B, underscores the severe impact of AKI on patient survival and highlights the critical need for proactive management of kidney function in myocardial infarction cases.